The cylinder amplitude in the hard dimer model on 2D Causal Dynamical Triangulations - Wheater, JF; Xavier, P (IOP Publishing, 2022)
We consider the model of hard dimers coupled to two-dimensional causal dynamical triangulations (CDT) with all dimer types present and solve it exactly subject to a single restriction. Depending on the dimer weights there are, in addition to the usual gravity phase of CDT, two tri-critical and two dense dimer phases. We establish the properties of these phases, computing their cylinder and disk amplitudes, and their scaling limits.